Approaches to sample size calculation for clinical trials in rare diseases. (10th January 2018) - Miller, Frank; Zohar, Sarah; Stallard, Nigel; Madan, Jason; Posch, Martin; Hee, Siew Wan; Pearce, Michael; Vågerö, Mårten; Day, Simon
Abstract : We discuss 3 alternative approaches to sample size calculation: traditional sample size calculation based on power to show a statistically significant effect, sample size calculation based on assurance, and sample size based on a decision‐theoretic approach. These approaches are compared head‐to‐head for clinical trial situations in rare diseases. Specifically, we consider 3 case studies of rare diseases (Lyell disease, adult‐onset Still disease, and cystic fibrosis) with the aim to plan the sample size for an upcoming clinical trial. We outline in detail the reasonable choice of parameters for these approaches for each of the 3 case studies and calculate sample sizes. We stress that the influence of the input parameters needs to be investigated in all approaches and recommend investigating different sample size approaches before deciding finally on the trial size. Highly influencing for the sample size are choice of treatment effect parameter in all approaches and the parameter for the additional cost of the new treatment in the decision‐theoretic approach. These should therefore be discussed extensively.